Toward a high-performance all-plastic full battery with a single organic polymer as both cathode and anode - Xie, Jian (2020)
The design and fabrication of high-performance all-plastic batteries is essentially important to achieve future flexible electronics. A major challenge in this field is the lack of stable and reliable soft organic electrodes with satisfactory performance. Here, a novel all-plastic-electrode based Li-ion battery with a single flexible bi-functional ladderized heterocyclic poly(quinone), (C6O2S2)n, as both cathode and anode is demonstrated. Benefiting from its unique ladder-like quinone and dithioether structure, the as-prepared polymer cathode shows a high energy density of 624 Wh kg−1 (vs lithium anode) and a stable battery life of 1000 cycles. Moreover, the as-fabricated symmetric full-battery delivers a large capacity of 249 mAh g−1 (at 20 mA g−1), a good capacity retention of 119 mAh g−1 after 250 cycles (at 1.0 A g−1) and a noteworthy energy density up to 276 Wh kg−1. The superior performance of poly(2,3-dithiino-1,4-benzoquinone)-based electrode rivals most of the state-of-the-art demonstrations on organic-based metal-ion shuttling batteries. The study provides an effective strategy to develop stable bi-functional electrode materials toward the next-generation of high performance all-plastic batteries.